2003
DOI: 10.1007/s00535-003-1198-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of gallstones by ursodeoxycholic acid after cardiac surgery

Abstract: The prophylactic administration of UDCA resulted in a significant decrease in the incidence of gallstones after open cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Oral administration of UDCA could prevent gallstone formation after bariatric surgery, because rapid weight loss increases the risk for gallstone formation (24). Ai et al (1) reported that oral administration of UDCA (600 mg/day) prevented the development of gallstones after cardiac surgery and that the prophylactic administration of UDCA could result in a significant decrease in the incidence of gallstones after open cardiac surgery. Although administration of UDCA failed to prevent sludge and/ or gallstone formation in mice without surgical manipulation, administration of UDCA might be effective after surgery even in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of UDCA could prevent gallstone formation after bariatric surgery, because rapid weight loss increases the risk for gallstone formation (24). Ai et al (1) reported that oral administration of UDCA (600 mg/day) prevented the development of gallstones after cardiac surgery and that the prophylactic administration of UDCA could result in a significant decrease in the incidence of gallstones after open cardiac surgery. Although administration of UDCA failed to prevent sludge and/ or gallstone formation in mice without surgical manipulation, administration of UDCA might be effective after surgery even in mice.…”
Section: Discussionmentioning
confidence: 99%
“…A protective effect of UDCA on hemolysis has been demonstrated in vitro. 12 However, Ai et al 1 did not find any significant difference in the indices of hemolysis during the early phase after surgery between patients with and without UDCA, a finding which does not support this possibility. Whether the deconjugation of bilirubin, or pH in bile is altered by UDCA was not examined.…”
mentioning
confidence: 94%
“…Thus, the effect of UDCA on GB contractility is probably not the major factor contributing to its effect on black GS. Ai et al 1 raised another possibility-that bile flow increased by UDCA may have played some role. Unfortunately, they did not mention whether UDCA reduced the incidence of biliary sludge before the detection of GS on ultrasohography.…”
mentioning
confidence: 98%
See 2 more Smart Citations